2013
DOI: 10.1088/0266-5611/29/11/115014
|View full text |Cite
|
Sign up to set email alerts
|

A geometric approach to joint inversion with applications to contaminant source zone characterization

Abstract: This paper presents a new joint inversion approach to shape-based inverse problems. Given two sets of data from distinct physical models, the main objective is to obtain a unified characterization of inclusions within the spatial domain of the physical properties to be reconstructed. Although our proposed method generally applies to many types of inverse problems, the main motivation here is to characterize subsurface contaminant source-zones by processing down gradient hydrological data and cross-gradient ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…Those authors then identified all unknown parameters using the adjoint-state equation approach. In a follow-on study, Aghasi et al 52 acknowledged the potential issue of local minima. A potential issue with such an approach is that different types of parameters may have 'aliasing effect' on each other (i.e., the result of adjusting weights may be equivalent to scaling the CSRBF or shifting the CSRBF centers), which in the worst case may even prevent the solution from converging.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…Those authors then identified all unknown parameters using the adjoint-state equation approach. In a follow-on study, Aghasi et al 52 acknowledged the potential issue of local minima. A potential issue with such an approach is that different types of parameters may have 'aliasing effect' on each other (i.e., the result of adjusting weights may be equivalent to scaling the CSRBF or shifting the CSRBF centers), which in the worst case may even prevent the solution from converging.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…In an explicit parametrization, this boundary has been described in terms of a spline basis [9,12,14] in two dimensions or with spherical harmonics [10] in three dimensions. In implicit formulations [6,[17][18][19], typically the shape unknowns are the values of the function sr on the reconstruction grid. In [17] with the objective of retaining an implicit representation coupled with significant search-space-dimensionality reduction (as in explicit schemes), we represent sr as a RBF via a Hermite interpolation scheme to fit a few on-curve points (called centers of the RBF, and denoted by r c 1 …r c m ) and the normal unit vectors at those points (denoted by n 1 …n m , where n i ≡ cos θ c i ; sin θ c i for some θ c i ).…”
Section: Problem Statementmentioning
confidence: 99%
“…While the first (explicit-representation) class of schemes (as in [9][10][11][12][13][14]) has the advantage of fewer unknowns, which is useful in potential threedimensional reconstructions, the second (implicitrepresentation) class [6,15,16] is better suited to handle topological changes in the evolving shape of the boundary. Radial basis function (RBF)-based implicit-representation reconstruction schemes were first suggested in [17] followed by recent works such as [18,19], extending the capability of the approaches in [10,14] by allowing for topological changes, while retaining their advantage over conventional implicitrepresentation schemes of having few unknowns. A detailed literature survey of these various classes of schemes is given in [10,13,14,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations